A randomized clinical trial to evaluate the single‐dose pharmacokinetics, pharmacodynamics, and safety of sitagliptin in pediatric patients with type 2 diabetes. Issue 1 (13th November 2018) - Fraser, Iain P.; Neufeld, Naomi D.; Fox, Larry A.; Kipnes, Mark S.; Miller, Tracie L.; Zeitler, Philip S.; Rodriguez, Henry; Gilmartin, Jocelyn H.; Lee, Susan J.; Patterson, Jaclyn K.; Li, Xiujiang S.; Maganti, Lata; et al.
Abstract : Objective: To evaluate the single‐dose pharmacokinetics (PK), pharmacodynamics (PD), and safety of sitagliptin in pediatric patients with type 2 diabetes mellitus (T2DM). Study Design: This was a randomized, placebo‐controlled, double‐blind evaluation of sitagliptin in 35 patients 10 to 17 years old with T2DM at 7 clinical research sites. The safety, tolerability, PK, and PD (dipeptidyl peptidase‐4 [DPP‐4] inhibition and aspects of glucose metabolism) of single doses of 50, 100, and 200 mg were assessed. Appropriate transformations on the PK parameters were used and back‐transformed summary statistics are reported. Results: Adverse experiences were reported by eight study participants; all were of mild intensity except one (intravenous site pain of moderate intensity). PK characteristics in the young patients were comparable to reference adult data, with geometric mean ratios (youths/adults) for AUC0−∞, Cmax, and C24hr of 0.82, 1.04, and 0.74, respectively. Single doses of 50, 100, and 200 mg sitagliptin inhibited 67.2%, 73.8%, and 81.2% of plasma DPP‐4 activity over 24 hours, respectively. Least squares (LS) mean glucose concentrations 2 hours after an oral glucose tolerance test or a meal tolerance test decreased in study participants treated with sitagliptin, compared to placebo, while active LS mean glucagon‐like peptide 1 concentrations increased significantly at all sitagliptin doses in both tests. Conclusions: Single doses of sitagliptin as high as 200 mg were generally well tolerated in 10‐ to 17‐year‐old male and female study participants with T2DM, and a daily sitagliptin dose of 100 mg is appropriate for evaluation in Phase III safety and efficacy studies in pediatric patients with T2DM. (ClinicalTrials.gov : NCT00730275).